Ground-state energy and entropy of the two-dimensional Edwards-Anderson spin-glass model with different bond distributions - Perez, Diego Javier; Ramirez Pastor, Antonio Jose; Romá, Federico José (Elsevier Science, 2012)
Fil: Perez, Diego Javier. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Comision Nacional de Energia Atomica. Gerencia del Area de Investigaciones y Aplicaciones no Nucleares. Gerencia de Fisica (CAB); Argentina